Is financial VAT neutral to financial sector size? - Julio López-Laborda; Guillermo Pe\~na (Kiel Institute for the World Economy (IfW), 2016)
The influence of the taxation of financial services in VAT on financial sector size is analyzed empirically. The authors use data from 36 countries of the European Union and the OECD for the period between 1961 and 2012. Dynamic panel data techniques are used, concretely the GMM System. An unbalanced panel is handled. The results allow them to support the theoretical analysis that states financial VAT has no significant effect on financial sector development, being neutral in relation to this variable. Results are robust to the specifications of the dependent variable.
Keywords: H25; H21; E62; E44; G21; 330; financial VAT; panel data; financial depth